[2 × 2] metallo-supramolecular grids based on 4, 6-bis((1H-1, 2, 3-triazol-4-yl)-pyridin-2-yl)-2-phenylpyrimidine ligands: from discrete [2 × 2] grid structures to star-shaped supramolecular polymeric architectures. Issue 25 (3rd June 2021) - Xu, Xiaowen; Seiffert, Anne K.; Lenaerts, Ruben; Ryskulova, Kanykei; Jana, Somdeb; Van Hecke, Kristof; Jerca, Valentin Victor; Hoogenboom, Richard
Abstract : [2 × 2] metallo-supramolecular grids were readily obtained by complexation of novel 4, 6-bis(6-ethynylpyridin-2-yl)-2-phenylpyrimidine ligands with Fe 2+ or Zn 2+ in acetonitrile, allowing for constructing discrete grids and star-shaped polymers. Abstract : The self-assembly of bis-tridentate ligands leads to the spontaneous formation of [2 × 2] grid-like metal complexes. However, the synthesis of such ligands is rather cumbersome. In the work, we demonstrate a straightforward synthesis route to prepare bis-tridentate 4, 6-bis((1 H -1, 2, 3-triazol-4-yl)-pyridin-2-yl)-2-phenylpyrimidine ligands through double CuAAC click chemistry with 4, 6-bis(6-ethynylpyridin-2-yl)-2-phenylpyrimidine as well as their self-assembly into [2 × 2] grid-like metal complexes. In addition, four macromolecular ligands were synthesized starting from azido-end-functionalized poly(2-ethyl-2-oxazoline) (PEtOx) or poly(ethylene glycol) (PEG). These macromolecular ligands were used in the construction of star-shaped supramolecular polymers through complexation with transition metal ions ( e.g., Fe 2+ or Zn 2+ ). The successful fabrication of complexes and star-shaped polymers was confirmed by UV-vis titration measurements and MALDI-TOF mass spectrometry. However, the chemical structure of the polymer was found to have a strong influence on the [2 × 2] grid formation, which was successful with the PEG-ligands but not with the PEtOx-ligands, while the molecular weight of the PEG did not interfere with grid formation.